Some perspectives on governance for development - Deshmukh, B.G. (2004)
From a nascent democracy established in early fifties, the national has made fast and veined strides in different areas of development. The system has coped well with the emerging issues and conditions. Yet it seems a little bit lethargic and lagging behind in consolidating its strengths and experiences. This article looks upon the issue of governance for development from various perspectives. With the passage of time radical transformation has set in the age old tenets of governance. The need of the hour is an agility to capture the trends in a more productive and integral manner. - Reproduced.
Keywords: Good governance